Untold Stories of the Spanish Civil War - Rain, Raʿanan 1960- HerausgeberIn; Zepp, Susanne 1973- HerausgeberIn (Routledge/Canada Blanch Studies on Contemporary Spain, 2024)
This is the first scholarly volume to offer an insight into the less known stories of women, children, and international volunteers in the Spanish Civil War. Special attention is given to volunteers of different historical experiences, especially Jews, and voices from less researched countries in the context of the Spanish war, such as Palestine and Turkey. Of an interdisciplinary nature, this volume brings together historians and literary scholars from different countries. Their research is based on newly found primary sources in both national and private archives, as well as on post-essentialist methodological insights for women’s history, Jewish history, and studies on belonging. By bringing together a group of emerging and senior scholars from different countries, we highlight the polyphony of voices of diverse individuals drawn into the Spanish Civil War. Contributors to this volume have explored new or little researched primary sources found in archives and documentary centers, including papers held by relatives of the people we study. The volume is aimed at both scholarly and non-scholarly public, including any readers interested in the Spanish Civil War, twentieth-century European history, Jewish studies, women’s history, or anti-Fascism. The volume can be used in both undergraduate college courses and in postgraduate university seminars